Is Percutaneous Cholecystostomy a Good Alternative Treatment for Acute Cholecystitis in High-Risk Patients?. Issue 6 (June 2017) - Papis, Davide; Khalifa, Eiman; Bhogal, Ricky; Nair, Amit; Khan, Saboor; Hamady, Zaed; Ahmed, Jawad; Marangoni, Gabriele
Cholecystectomy is the treatment of choice for acute cholecystitis but the management of high-risk surgical patients is a difficult dilemma. Percutaneous cholecystostomy (PC) could represent a safer and less invasive option. The aim of the study was to assess the outcomes of PC in high-risk patients. This is a retrospective single-center study; data were collected from our hospital electronic record system. From February 2009 to March 2014, there were 753 patients admitted with acute cholecystitis. Of these 39 were considered high risk for surgery and underwent PC during their hospital stay. The radiological approach was transperitoneal in 29 patients and transhepatic in 10 patients. Median follow-up was 19 months. There were 27 males (69.2%) and 12 females (30.8%) with a mean age of 72 years (range 41–90 years). Twenty-seven patients had PC as definitive treatment (group A) and 12 patients as a bridge to cholecystectomy (group B). There were no postprocedure complications. Five patients in group A were readmitted once with another episode of cholecystitis after PC (18.5%), one patient in group B was readmitted with cholecystitis after two years before proceeding to cholecystectomy, and two patients were readmitted after cholecystectomy (16.6%) for intra-abdominal collections treated with percutaneous radiological drainage. Seven patients died (17.9%) as a result of severe biliary sepsis during their index hospital admission. PC is a safe approach in high-risk patients with acute cholecystitis and can provide satisfactory long-term results when cholecystectomy is not a viable option.